Trials on commercial silage additives - K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1982)
Numerous commercial silage additives, manufacturers of which make various claims for their improving silage quality, are available to Kansas farmers and ranchers. In 2 previous years (1980 and 1981), we reported on nine trials involving six additives (Progress Reports 377 and 394). Each additive improved the silage in at least one of the four criteria we evaluated: 1) ensiling temperature, 2) dry matter recovery, 3) feeding value, and 4) aerobic stability. Two more trials with additives are reported on in this Progress Report (pages 6 and 11 ).
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Silage; Quality; Dry matter